City States in the Later Medieval Mediterranean World. Issue 1 (13th October 2021) - Lantschner, Patrick
Abstract: This article offers a comparative study of city states in the Christian and Islamic spheres of the later medieval Mediterranean world, with a particular focus on Italy, Syria and al-Andalus. Medieval city states are not usually associated with the Islamic world, but rather with a narrative that has foregrounded the exceptional nature of European cities in world history, especially the famous city republics in Northern and Central Italy, and the role that city states played in the formation of European states. Yet city states were a phenomenon that could be observed across urbanized regions of the Mediterranean world where cities turned into important political arenas in the context of sustained political fragmentation. City states are best approached as political systems that were characterized by brittle regimes and experienced high levels of political volatility: they often lacked a clear boundary between the 'inside' and 'outside' of city states and were characterized by the multiple political organizations that crystallized in, and fought hard to control, urban political space. The most commonly shared type of political organization in city states was the urban lordship, but city-based lords usually found themselves in intense competition with elite-based collective associations, families and factions, and popular political organizations.